Examining relationships between sub-components of reading in Xitsonga - Khosa, Martha (Academy Publication, 2024)
Reading is developed over time and involves the interaction of both simple and complex skills characterised by a hierarchical sequence of foundational reading skills. However, research has shown that children who do not acquire mastery of foundational reading skills have limited chances of acquiring reading success. This study examines the relations between sub-components of reading in Xitsonga and their impact on Grade 1 learners’ reading ability. It also aims to identify which early reading skills predict later reading accomplishment. Data in this study was obtained from 75 Grade 1 learners in the Limpopo Province. The early-grade reading assessment tool adapted to Xitsonga was used to test the learners’ foundational reading skills: phonological and phonemic awareness, letter-sound knowledge, word reading, oral reading fluency and reading comprehension skills. The results present a compelling relationship between the subcomponents of reading and show that deficits in the development of foundational reading skills negatively impact learners’ ability to read. Regression analysis showed that oral reading fluency was the only significant predictor of reading comprehension. Hence, there is a need for reading to be taught and learned consciously in alphabetic languages to help learners develop their early reading skills, which play important roles in the acquisition of reading.
Keywords: Xitsonga; foundational reading skills; sub-components of reading; early grade reading